Does Value Added of Intellectual Capital Influence Voluntary Disclosure? The Moderating Effect of CSR Practices - Jamel Chouaibi; Salim Chouaibi (Journal of Accounting and Management Information Systems (JAMIS), 2020)
Research Question: Does the effect of corporate social responsibility (CSR) practices and value added of intellectual capital (VAIC), is contingent on the intellectual capital (IC) information disclosure policy adoption in the Environmental, Social and Governance (ESG) companies? Does CSR have a moderating effect on the relationship between VAIC and IC disclosure? Motivation - The majority of the literature has examined the effect of value added and social responsibility on the overall transparency of the business while neglecting their effect on the voluntary intellectual capital disclosure. Our study seeks to fill this gap by testing the moderating effect of socially responsible practices on the relationship between VAIC and voluntary IC disclosure. This paper is the first comprehensive attempt to analyses the interaction between CSR practices and VAIC with voluntary IC disclosure. Idea - This study examines how CSR practices moderate the relationship between the added value of intellectual capital (VAIC) and voluntary disclosure of IC in the world's most committed ESG companies in business ethics. Data - The data were collected from Thomson Reuters ASSET4 database from four countries to analyze data of 153 listed companies selected from the Environmental, Social and Governance (ESG) index between 2015 and 2019. Tools - To test study's hypotheses, we applied linear regression with a panel data using the Thomson Reuters ASSET4 database. Findings - Two main results can be derived: First, the integration of CSR into company strategy is positively associated with voluntary IC disclosure. Second, the interaction between CSR practices and VAIC is a determinant of this type of disclosure to reduce the asymmetry of information and the conflict of interest. Contribution - The majority of the literature has examined the effect of value added and social responsibility on the overall transparency of the business while neglecting their effect on the voluntary intellectual capital disclosure. Our study seeks to fill this gap by testing the moderating effect of socially responsible practices on the relationship between VAIC and voluntary IC disclosure. This paper is the first comprehensive attempt to analyses the interaction between CSR practices and VAIC with voluntary IC disclosure.
Keywords: M41; 650; corporate social responsibility (CSR); moderating effect of CSR; value added of intellectual capital (VAIC); voluntary disclosure; Intellectual Capital (IC).